1979
DOI: 10.1080/10862967909547313
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Imaginal and Verbal Strategies on Prose Comprehension by Adults

Abstract: Abstract. Adult subjects were given concrete and abstract textbook passages to study by using either an imaginai or verbal strategy. Two days later, they were given a multiple-choice test and a production test of comprehension. The verbal strategy produced better comprehension than the imaginai strategy; concrete passages were comprehended better than abstract passages, but only according to the production test; and strategy and concreteness did not interact. Differences between these results and results obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

1981
1981
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 19 publications
2
8
0
Order By: Relevance
“…A second study, that of Tirre et al (1979), is also inconsistent with the assessment hypothesis though only superficially so. College students read short, expository texts that presented three different target objects.…”
Section: The Benefits Of Drawing Construction Are Revealed On Higher-mentioning
confidence: 65%
See 1 more Smart Citation
“…A second study, that of Tirre et al (1979), is also inconsistent with the assessment hypothesis though only superficially so. College students read short, expository texts that presented three different target objects.…”
Section: The Benefits Of Drawing Construction Are Revealed On Higher-mentioning
confidence: 65%
“…Although we believe this study points out a limitation of the strategy, as does the study by Hall et al (1997), we do not consider the study by Tirre et al (1979) to be a reasonable test of the strategy. In Tirre et al's study, the problem lies in the poor match between the strategy and the task.…”
Section: The Benefits Of Drawing Construction Are Revealed On Higher-mentioning
confidence: 96%
“…Finally, illustrating passage content does not always facilitate learning of the material. Compared to a group using a verbal learning strategy (paraphrasing), learners who illustrated concepts in passages from a number of subject areas did not perform as well (Tirre, Manelis, and Leicht, 1979). Taken together, the studies on learner-drawn pictures offer weak support favoring this pictorial strategy.…”
Section: Learner-drawn Picturesmentioning
confidence: 89%
“…Some theorists have suggested that imagery as well as verbal processes might be involved in the composition of text, implicating concreteness as a semantic factor in composing (Flower & Hayes, 1984; Sadoski, 1992). In an empirical study, Tirre, Manelis, and Leicht (1979)assigned undergraduates to use either a verbal or an imagery strategy in reading concrete and abstract passages matched for comprehensibility. When students were asked to explain in writing how a set of content words from each passage were related, passage concreteness had a significant effect on quality, although strategy assignment did not.…”
mentioning
confidence: 99%